Blog experience as a didactic resource in the Introduction to Newtonian Physics - Calle Chumo, Rafael Norberto (2022)
This research has verified the use of technologies in an educational environment assisted by blog, which institutes the management and appropriation of digital tools in teaching skills, with a qualitative research methodology, supported and executed through an interview for teachers and students. Evaluating the blog experience during an Introduction to Newtonian Physics module for high school students, generated an analytical extension towards the different educational settings. Therefore, the investigative scope supports the use of digital resources for the unification of theoretical and practical components; mediated by digital tools and / or simulations. In summary, this didactic resource incorporated guidelines on active learning into teacher instruction, emphasizing the potentialization of digital skills.